1996
DOI: 10.1088/0264-9381/13/3/002
|View full text |Cite
|
Sign up to set email alerts
|

Solution-generating transformations and the string effective action

Abstract: We study exhaustively the solution-generating transformations (dualities) that occur in the context of the low-energy effective action of superstring theory.We first consider target-space duality ("T duality") transformations in absence of vector fields. We find that for one isometry the full duality group is (SO ↑ (1, 1)) 3 × D 4 , the discrete part (D 4 ) being non-Abelian. We, then, include non-Abelian Yang-Mills fields and find the corresponding generalization of the T duality transformations. We study the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
177
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(184 citation statements)
references
References 42 publications
7
177
0
Order By: Relevance
“…Instead, fields that transform as usual (i.e.à la Buscher [23,24]) under T-dualities, and more generally under O(d, d), involve non-covariant redefinitions. A similar result was obtained for the heterotic string in [25], where the O(d, d) friendly fields were obtained through a Lorentz non-covariant redefinition of the metric in terms of the spin connection with torsion (a similar result involving gauge fields was recently found in [26]). Such redefinition had been previously considered in [27], where it was shown that the usual Green-Schwarz mechanism of anomaly cancellation [28] is only consistent with worldsheet supersymmetry if the metric is non-covariantly redefined.…”
Section: Jhep10(2015)084supporting
confidence: 74%
See 1 more Smart Citation
“…Instead, fields that transform as usual (i.e.à la Buscher [23,24]) under T-dualities, and more generally under O(d, d), involve non-covariant redefinitions. A similar result was obtained for the heterotic string in [25], where the O(d, d) friendly fields were obtained through a Lorentz non-covariant redefinition of the metric in terms of the spin connection with torsion (a similar result involving gauge fields was recently found in [26]). Such redefinition had been previously considered in [27], where it was shown that the usual Green-Schwarz mechanism of anomaly cancellation [28] is only consistent with worldsheet supersymmetry if the metric is non-covariantly redefined.…”
Section: Jhep10(2015)084supporting
confidence: 74%
“…Regarding the heterotic case (a, b) = (−α ′ , 0), our results predict the field redefinitions of [25] that relate the Lorentz-covariant metric with the T-duality covariant one. In addition, we obtain the anomalous Lorentz transformation of the metric as given in [27], plus the usual Green-Schwarz transformation of the two-form in terms of ω (−) .…”
Section: Jhep10(2015)084mentioning
confidence: 54%
“…Notably, the Yang-Mills gauge field enters into the space-time action as the first order α ′ -corrections. Due to the α ′ -corrections, the Buscher rule [25,26] of the T-duality transformation for heterotic supergravity is modified [27][28][29]. The most famous extended objects in heterotic supergravity theories are the heterotic NS5-brane solutions.…”
Section: Jhep11(2016)064mentioning
confidence: 99%
“…Since the gauge field enters into the action (2.1) as the first order α ′ -correction, the T-duality transformation in the heterotic supergravity should be modified from the standard Buscher rule [25,26]. The first order α ′ -corrections to the Buscher rule in heterotic supergravity have been written down in [28]. This is given by…”
Section: T-duality Chains Of Five-branes and α ′ -Corrected Buscher Rulementioning
confidence: 99%
“…In this way, it is easy to see that the last equation is covariant under linear combinations of the vector fields and the S dual vector fields 21) with the only requirement that the transformation matrix is non-singular. However, these vector fields are not independent and consistency implies the following non-linear transformations for the complex scalarλ…”
Section: S Duality Transformationsmentioning
confidence: 99%